The effect of body mass index on bone mineral density in postmenopausal women - Gürlek, Yusuf Serdar; Kalaycıoğlu, Ahmet; Gurlek, Beril (International Journal of Research in Medical Sciences, 2018)
Background: The aim of this study was to evaluate the association between BMI and BMD among postmenopausal women. Methods: A total of 121 healthy female patients, aged 65.67±8.59 years, previously menopaused, were enrolled. Subjects were divided into five subgroups according to their BMI. History of fracture and BMD were recorded and compared between groups. Results: Among the 121 subjects, 77 (63.6%) individuals had a normal BMD, 32 (26.4%) had osteopenia, and 12 (9.9%) were diagnosed with osteoporosis. Mean of waist circumference was 96.1±8.52cm. The prevalence of fractures was 29.8% in this study. A simple correlation analysis revealed that waist circumference was negatively related to lumbar spine BMD (r= -0.374, p=0.03) and lumbar spine BMD T score (r= -0,352 p=0.002) whereas body weight was positively related to BMD of lumbar spine BMD (r=0.41, p=0.0001) and lumbar spine BMD T score (r=0,31 p=0.001). Age and years since menopause (YSM) were negatively correlated with BMD and T score (p=0.001, p=0.0001, respectively). Conclusions: Even though higher BMI seems to have positive impact on bone density thanks to hormonal and mechanical reasons, increased waist circumference is a sign of a metabolic syndrome and systemic inflammation which are known as having negative effect on bone density. Therefore, postmenopausal women specifically with abdominal obesity should be evaluated for osteoporosis.